Quality Management System Practices Performed in ISO 9001 Certified Engineering Educational Institutions : A Critical Analysis of Indian Universities - Kumar, Parvesh; Singhal, Sandeep; Kansal, Jimmy (Journal of Engineering Education Transformations, 2022)
This study aims to analyse the quality management system (QMS) practices performed in ISO 9001 certified engineering educational institutes of India. The literature divulged that QMS in engineering education mainly engrossed on teaching, learning, examinations, student results and infrastructure. Very few studies mentioned QMS in terms of organizational effectiveness. Thus the author has conducted the QMS analysis in forty-five engineering educational institutions (EEIs) of Delhi NCR area in India and selected two groups of institutions based on years of existence. Group-a consists of twenty institutions less than fifteen years old, and group-b consists of twenty-five institutions over fifteen years old. Data were collected using a questionnaire from forty-five engineering educational institutions. The questionnaire was prepared using QMS constructs (ten factors) followed by the institutions and the quality measures followed by the national board of accreditation-NBA in India. Data analysis was done using SPSS 26.0 software to conclude the student t-test and p-value. The author found that the group-b institutions received substantially higher scores in variables that had top management commitment, systemic management approach, customer satisfaction, employee involvement, training, teamwork, continuous improvement, corporate social responsibility, academic culture and knowledge audit compared to group-a institutions. The study also revealed the strong and weak points of the institutional QMS, and there is a strong need to incorporate ISO 9001:2015-based QMS practices for the continuous improvement of institutions.